Quantitative analysis to measure the impact of mindfulness practice in primary school students on their academic performance. - Benesh Fernández-Miranda, Nicolás (Journal of Learning Styles, 2023)
This study shares the results of a quantitative research study with students in the 5th year of Primary Education through the analysis of the academic performance of the students in this experimental group and its contrast with another control group from a different school through the non-parametric statistical tests applied, Mann Whitney U and Wilcoxon. Through the analysis of the scores from the pre-test and post-test approach, it is observed how a few minutes of mindfulness practice before the assessment tests, together with the weekly performance of two sessions of longer duration, allows students in the experimental group to approach them with greater calm, serenity and confidence in their own possibilities, moving away from the nervousness and possible anxiety that these may cause. Through the exploratory analysis, it is easy to understand the evolution and improvement of the students’ academic performance, which, contrasted with the aforementioned statistical tests, shows the improvement in the academic performance of the experimental group.